How ‘Ought’ the Best Interests of Children be Considered in Medical Decision-making? - Ritchie, Zoe; Forte, Micaela; Smith, Maxwell; Shelley, Jacob (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
This summary reports on the design and proceedings of a collaborative case-based workshop and panel on how we ‘ought’ to consider the best interests of children in medical decision-making, presented virtually at the Canadian Bioethics Society - Société Canadienne de Bioéthique Workshop and Community Forum in May of 2023.